(untitled) (Innovative professional education, 2023)
In the conditions of martial law and the need to rebuild the destroyed economy, preparing young people for entrepreneurial activity is an extremely important task of the professional education system. Consulting on youth entrepreneurship requires the creation of an appropriate information space, the filling of its content, the provision of various high-quality consulting services and the use of the latest forms of work.